Are B cells altered in the decidua of women with preterm or term labor?. (29th March 2019) - Leng, Yaozhu; Romero, Roberto; Xu, Yi; Galaz, Jose; Slutsky, Rebecca; Arenas‐Hernandez, Marcia; Garcia‐Flores, Valeria; Motomura, Kenichiro; Hassan, Sonia S.; Reboldi, Andrea; Gomez‐Lopez, Nardhy
Abstract : Problem: The immunophenotype of B cells at the maternal‐fetal interface (decidua) in labor at term and preterm labor is poorly understood. Method of study: Decidual tissues were obtained from women with preterm or term labor and from non‐labor gestational age‐matched controls. Immunophenotyping of decidual B cells was performed using multicolor flow cytometry. Results: (a) In the absence of acute or chronic chorioamnionitis, total B cells were more abundant in the decidua parietalis of women who delivered preterm than in those who delivered at term, regardless of the presence of labor; (b) decidual transitional and naïve B cells were the most abundant B‐cell subsets; (c) decidual B1 B cells were increased in women with either labor at term or preterm labor and chronic chorioamnionitis compared to those without this placental lesion; (d) decidual transitional B cells were reduced in women with preterm labor compared to those without labor; (e) naïve, class‐switched, and non–class‐switched B cells in the decidual tissues underwent mild alterations with the process of preterm labor; (f) decidual plasmablasts seemed to increase in women with either labor at term or preterm labor with chronic chorioamnionitis; and (g) decidual B cells expressed high levels of interleukin (IL)‐12, IL‐6, and/or IL‐35. Conclusion: Total B cells are not increased with the presence of preterm or term labor; yet, specific subsets (B1 and plasmablasts) undergo alterations in women with chronic chorioamnionitis. Therefore, B cells are solely implicated in the pathological process of preterm labor in a subset of women with chronic inflammation of the placenta. These findings provide insight into the immunology of the maternal‐fetal interface in preterm and term labor.